Structural solutions based on intensive use of steel for over-roofing of existing precast concrete panel buildings. Issue 12 (December 2016) - Floricel, Andra; Zagari, Giuseppe; Ungureanu, Viorel; Ciutina, Adrian
An important segment of the Romanian urban population, similar to other Eastern European countries, lives in collective residential apartment buildings made using large prefabricated concrete panels. Most of these structures were built between 1960 and 1989 and present major issues concerning aesthetical aspects, lack of internal space, problems related to thermal comfort and, last but not least, weak energy efficiency. The presence of flat roofing system, generally with hydrothermal faults, represents an additional problem which leads to deficient living conditions of the last-storey inhabitants in many cases. Besides other ways of improving the conditions of such apartment houses, the over-roofing is welcome in order to both increase the habitable area and provide adequate roofing for the building. This article presents three types of over-roofing structural solutions, in two solutions, based on intensive use of steel, using (1) hot-rolled steel profiles, (2) rectangular hollow sections and (3) cold-formed steel profiles, respectively. In order to determine the optimum over-roofing system, the study analyses the structural design possibilities and particularly the connection between the new and old structural elements.